On the Consequential Validity of ESP Tests: A Qualitative Study in Iran - Gholam Reza Kiani; Goodarz Alibakhshi; Ramin Akbari (Journal of Applied Linguistics, 2009)
Consequential validity, a component of construct validity as a unified concept introduced by Messick(1989), deals with the impacts of tests on teaching, learning, individual test takers, teachers, society, and educational system within a country. Although the impacts of language tests on teaching and learning have been somehow studied, the consequences of ESP tests on individual test takers and teachers have not been given appropriate attention. The present study aimed at exploring the possible consequences of ESP tests, as parts of master and doctoral entrance examinations to post graduate universities in Iran, on the stake holders and society. In doing so, a qualitative research method was applied. The participants were 31 master and doctoral students, and 5 ESP instructors. The data were analyzed in terms of the content. Four main themes with a variety of sub-themes emerged from the content analysis. The results indicated that ESP tests have negative psychological (anxiety, stress, disappointment, self-confidence, teaching efficacy, disappointment), social (deprivation from education, ethical issues, acceptance of nonqualified candidates), financial, and family consequences on the learners and teachers. The society is also influenced as the result of ESP tests scores.